Using the lichen Parmelia sulcata Taylor in the urban environment monitoring (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The article presents the results of the long-term research of the lichen species population in urban environment. The tolerant species Parmelia sulcata Taylor was chosen as an indicator of urban conditions. The study was conducted in different parts of the city of Pskov (Russia) varying in degree of air pollution. The analyses of species’ urban habitats, substrate diversity, thalli location in relation to the points of the compass, abundance and projective cover are discussed. Attention is also focused on the morphological parameters of the lichen’s thalli (thalli size, presence or absence of apothecia, vegetative propagules, thalli color and presence of necro spots on the lichen individuals etc.) in different environmental conditions. Received data will serve as a base for monitoring Parmelia sulcata population change continuously.